Growth Performances and Carcass Characteristics of Broiler Chickens Fed Akasya [Samanea Saman (Jacq.) Merr.] Pod Meal - Reyes, F. C. C.; Aguirre, A. T. A.; Agbisit Jr, E. M.; Merca, F. E.; Manulat, G. L.; Angeles, A. A. (Tropical Animal Science Journal, 2018)
Akasya pods are seasonally abundant and are good sources of protein and energy and have been considered as an alternative feed source for livestock. This study was conducted to determine the effects of feeding Akasya pod meal (APM) on the growth performances and carcass characteristics of broiler chickens. Three hundred straight-run 7-day-old Cobb broiler chicks were randomly allocated to five dietary treatments containing 0%, 0.5%, 1.0%, 2.5%, and 5.0% APM following a completely randomized design. Each treatment was replicated 10 times with 10 birds per replicate. The digestibility of nutrients was also evaluated to determine the effect of different levels of APM on the efficiency of nutrient digestion in broilers. Broilers fed APM level at more than 1.0% had lower body weights and body weight gains, but feed intake, feed conversion ratio, livability, and carcass characteristics were not affected by increasing levels of APM. The digestibility of crude protein (CP), crude fiber (CF), nitrogen free extract (NFE), ether extract (EE), and energy were the same in broilers across treatments. Increased income over chick and feed cost (IOFCC) was generated from broilers fed diets with 0.5% APM, but progressively declined as APM level in the diet was increased. In conclusion, APM can be used in broiler diets at inclusion levels up to 1.0% wherein growth performance and carcass characteristics were optimum in broilers and income generated was improved at 0.5% level.